(untitled) (Economics and region, 2022)
The article focuses on the main problems of the of the heat and power complex that arose in connection with the war in the country, deterioration of the main power grids, lack of sufficient funds in the budget, and imperfect legislation. Due to the above problems, heat and power companies suffer serious losses and need support and control by the state. The importance of conducting an audit of activity efficiency is substantiated of business entities of the thermal energy complex, monitoring possible cases of theft, bribery, fraud, abuse official position of management. In order to prevent such negative phenomena, as well as to create opportunities to support subjects management, it is necessary to conduct a high-quality state financial audit. It is with the help of the state financial audit that it is possible to track directions of receipt and expenditure of state resources, their rationality use, effectiveness of management decision-making. It is noted that the State financial audit of economic entities of the public sector of the economy should be conducted annually, since they are of strategic importance for the economy and security of the state. The author analyzes the methodological techniques necessary for auditing specific objects of activity of an economic entity of the heat and power complex. The process and results of the State financial audit of economic entities in the heat and power sector are analyzed on the example of the municipal enterprise of heat networks "Ternopilmiskteplocomunenergo" of the Ternopil City Council, which supplies heat energy and provides district heating and centralized hot water supply services to the population and other consumers of Ternopil. The necessity of state support for economic entities of the heat and power complex is substantiated. The importance of the State financial audit for timely identification of possible risk factors in the work of enterprises and minimizing them, improving the efficiency and quality of the heat and power complex as a whole, rational use of public resources, efficiency of management decision-making, timeliness of detection of violations at various levels of budgetary funds management is indicated. It is concluded that the improvement and development of the state financial audit of economic entities of the heat and power complex is is an important task for the state.